Techniques of social influence : The psychology of gaining compliance (2016)
As a rule, the introduction is where the author explains to the reader what the book is about. Before I do that, however, I will take the liberty of a brief digression of a personal nature. Whenever I’m at some sort of gathering and find I am acquainted only with the host, my interactions with other guests go off “without a hitch”. I’m not a particularly shy person, so it’s rather easy for me to get to know others and to talk to them about more or less serious subjects. Problems begin when they ask me what I do for a living. My answer – that I am a psychologist – provokes a feeling of unease in my interlocutors. “So you must be observing us and analyzing,” I hear. “What do you think about us?” My answer, that I’m not observing or analyzing anybody but, just like everybody else, having a beer, chatting about Almodóvar’s latest film, Kundera’s books, recent sports events or political happenings, isn’t taken at face value by others. It gets worse when the conversation turns to questions like “So what is it you do exactly? Do you put people through psychotherapy, or devise intelligence tests?” I respond that I’m not a therapist and that I’ve never created any intelligence test, and nothing would indicate that I ever will. I explain that for many years I have been engaged in the study of social influence techniques. When I give a few examples by way of explanation, opinions about me are uniformly devastating: I am a guy who sits in a lab and dreams up schemes for effectively manipulating people. As it is, psychologists concerned with social influence techniques usually aren’t thinking up new tricks. Our approach to the subject is just the opposite. The metaphor of full-cycle social psychology, applied by Robert Cialdini (1980), would seem to be a good illustration of this. The full cycle is a construction under which a social influence technique emerges in social life, and after it is “discovered”, investigated and described by scientists, it winds up back in that “real life”. So, a psychologist interested in these techniques observes the tricks applied by individuals whose professions or social roles involve them exerting influence on others.